Cochrane Corner - Telephone interventions for educational and psychosocial support for informal caregivers - Henriques, Adriana (2023)
The telephone is an easy way for health professionals to provide educational and psychosocial support to informal caregivers. This Cochrane systematic review evaluated 21 randomized clinical trials involving 1,690 caregivers comparing the efficacy of telephone interventions against usual care, regarding educational and psychosocial support. It was concluded that these interventions may have a slight benefit for some outcomes, such as reducing anxiety and improving preparation for care. However, for most of the evaluated outcomes, the additional effect of using telephone interventions was little or none. Most studies had a high risk of bias and few participants.